Changes of Microbiome in Human Papillomavirus Infection and Cervical Cancer: A Systematic Review and Meta‐Analysis - Wei Zhang; Yan Ge; Lihe Yao; Qingchun Yan; Jiuju Wei; Yanfei Yin; Bin Liu (Cancer Reports)
ABSTRACT Background and Objectives We aimed to conduct a systematic review and meta‐analysis of high‐throughput sequencing studies to assess changes in microbiome alpha, beta diversity, and composition differences in patients with human papillomavirus (HPV) infection and cervical cancer. Methods The PubMed, Embase, Web of Science, and Cochrane Library databases were systematically searched to include original studies. The effect size estimates with a 95% confidence interval were combined using a random effects model. The meta‐analysis was performed using the Stata MP16 software. Results A total of 64 studies were included, with a meta‐analysis of the diversity index performed on a subset of seven studies. Microbial diversity of patients infected with HPV was observed to be significantly different from that of healthy controls (CHAO index: 95% CI 0.42, 5.03, I2 = 99.18%, p < 0.05). Subgroup analysis based on the sample collection region showed a significant difference between vaginal microbiota of the treatment group and control group, as measured by the Shannon index (95% CI 0.12, 0.97, I2 = 67.09%, p < 0.05). Further, subgroup analysis of samples sequenced with the primer pair for the V3–V4 region showed a statistically significant difference in alpha diversity (Shannon index: 95% CI 0.28, 0.72, I2 = 0.00%, p < 0.05) between treatment and control groups. The microbial diversity varied between patients with inferior cervical lesions (low‐grade squamous intraepithelial lesion) and healthy controls (Shannon index: 95% CI 0.02, 0.58, I2 = 0.00%, p < 0.05). The bacterial marker genera differed at each cervical lesion stage. Gardnerella was prevalent during the HPV infection stage, but its proportion decreased after the occurrence of cervical lesions. In contrast, the proportions of Prevotella, Porphyromonas, and Dialister increased during the cervical cancer stages. Conclusions Patients with simple HPV infections frequently exhibit unstable microbial diversity and are influenced by various factors. The microbial environment continues to change after the occurrence of cervical lesions and is correlated with the severity of cervical lesions.